Melons: Safe Handling Practices for Consumers - Amy Simonne (EDIS)
Since most of us buy melons at the store or farmers market, it is easy to forget that most melons are grown on the ground. Watermelons, cantaloupe, and honeydew melon are the most popular varieties of melons in the United States. Because they are exposed to pests and microorganisms from dirt, it is very important to apply the best food safety practices before enjoying them. This 3-page fact sheet was written by Amy Simonne, and published by the UF Department of Family Youth and Community Sciences, June 2013.